ANALISIS KEUNTUNGAN USAHA MINUMAN HERBAL INSTAN “JAKULAWAK” DI DESA SINSINGON BARAT KECAMATAN PASSI TIMUR KEBUPATEN BOLAANG MONGONDOW (Analysis of Business Profits of Instant Herbal Beverage "Jakulawak" In West Sinsingon Village, Passi Timur Sub Distric) - Gracia Injilia Tambayong; Audrey J. M. Maweikere; Noortje M. Benu (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2022)
The objective of this research is to calculate and analyze the profits of the "Jakulawa" instant herbal drink business. The research method used is a case study in the UMKM instant herbal drink "Jakulawa". Data used in March 2022. Data collection in this study used interviews and documentation. The interview was conducted by directly interviewing the owner of the instant herbal drink "Jakulawa" as a respondent using a questionnaire that had been prepared previously (questionnaire). Documentation is done by collecting data related to research both from related agencies and the internet. The results of the research showed that the "Jakulawa" instant herbal drink business incurs a total production cost of IDR 569,721. The profit earned by the "Jakulawa" instant herbal drink business in March 2022 was Rp. 880,279, with an R/C value of 2.54 which means this business is profitable.